Phase equilibria description of biodiesels with water and alcohols for the optimal design of the production and purification process - Oliveira, Mariana B.
The water solubility in fatty acid esters and biodiesels and the vapor-liquid equilibria (VLE) of fatty acid ester + methanol/ethanol systems, formed at biodiesel production and purification industrial units, were modeled in this work to complete the development and application of the soft-SAFT equation of state (EoS) to the design and optimization of biodiesel production plants. The soft-SAFT EoS is able to accurately describe the water solubility and the VLE of methanol and ethanol with a large number of binary systems, composed of a variety of esters, in wide ranges of temperature, including near/supercritical conditions, with the use of just one binary interaction parameter. This parameter is chain length dependent for the water systems, while it is constant for the methanol and the ethanol binary mixtures. An entirely predictive scheme is proposed for the soft-SAFT EoS water solubility in biodiesels description, being only necessary to know the biodiesel fatty acid esters composition to determine the required molecular and binary interaction parameters. A new association scheme to explicitly consider the solvation phenomenon between esters and water/alcohols is also proposed. The results obtained in this work with soft-SAFT are clearly superior, regarding qualitative and quantitative agreement with the experimental data and predictive ability of the model, to those obtained with other similar modeling approaches, namely with the Cubic-plus-Association equation of state (CPA EoS) and other SAFT-type EoSs, as discussed throughout the work. The soft-SAFT EoS is shown here as a valuable tool to assist the design of biodiesel purification units, specifically for applications in the biodiesel washing, drying and alcohol removal, in order to obtain the biodiesel with the quality specifications required by the international standards. (C) 2014 Elsevier Ltd. All rights reserved.